2016
DOI: 10.1002/2016wr019047
|View full text |Cite
|
Sign up to set email alerts
|

Fate and transport of dissolved methane and ethane in cretaceous shales of the Williston Basin, Canada

Abstract: Baseline characteristics of dissolved methane (CH4) and ethane (C2H6) and their stable isotopes in thick, low hydraulic conductivity, Cretaceous shales were determined using high‐resolution core profiling at four sites in the Williston Basin (WB), Canada. Positive correlations with the conservative natural tracer Cl− reflected a lack of measureable production or consumption of gases in the shale to the depth investigated (150 m below ground, BG) and suggest CH4 and C2H6 concentrations near the interface with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
(69 reference statements)
4
15
0
Order By: Relevance
“…Given that Cl − is a conservative species, these strong linear relationships suggest, on the whole, the same transport mechanism is operative for both Cl − and CH 4 with no indication of losses of CH 4 from biogeochemical activity (i.e., no production or removal) in the CH 4 concentration-depth profiles in the till and shale. The lack of sorption-desorption reactions for CH 4 is supported by laboratory experiments and consistent with low concentrations of total organic carbon in the Pierre Shale (~0.8% wt) 16 .…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Given that Cl − is a conservative species, these strong linear relationships suggest, on the whole, the same transport mechanism is operative for both Cl − and CH 4 with no indication of losses of CH 4 from biogeochemical activity (i.e., no production or removal) in the CH 4 concentration-depth profiles in the till and shale. The lack of sorption-desorption reactions for CH 4 is supported by laboratory experiments and consistent with low concentrations of total organic carbon in the Pierre Shale (~0.8% wt) 16 .…”
Section: Introductionsupporting
confidence: 58%
“…The value of n e for CH 4 was assumed to be equal to the total porosity ( n T ) 51 . The n e values for Cl − were determined to be n e  =  n T for the till and n e  = 0.7 n T for the Pierre Shale Fm 16 . The value of D e for 12 C-CH 4 was assumed to be the same as that for CH 4 transport in the shale (2.4 × 10 −10 m 2 s −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…43,44 To a lesser extent, saline formation waters associated with hydrocarbons can also migrate into near-surface environments. 45 Fluid migration pathways between and among source rocks, reservoirs, and shallow aquifers, can exist naturally (e.g., along faults of multiple scales, or through fractured formations; Figure 1) and identifying sources and conduits can be complex. They can include multiple gas sources generated in the subsurface by abiotic, thermogenic and/or microbial processes, which can be mixed within geologic formations (source rocks or reservoirs) or along migration pathways in the absence of any drilling or HVHF activities.…”
Section: Introductionmentioning
confidence: 99%
“…It can be confirmed from almost the same results that high sulfate (0.3-48.7 g/L with mean 6.1 g/L) concentrations in the porewater. It has been reported that there are high sulphate concentrations in clay porewater in North Mexico [5] and Belgium [6].…”
Section: Resultsmentioning
confidence: 99%